Hydrogen peroxide is generated systemically in plant leaves by wounding and systemin via the octadecanoid pathway - Orozco-Cardenas, Martha (The National Academy of Sciences, 1999)
Hydrogen peroxide (H(2)O(2)) generated in response to wounding can be detected at wound sites and in distal leaf veins within 1 hr after wounding. The response is systemic and maximizes at about 4–6 hr in both wounded and unwounded leaves, and then declines. The timing of the response corresponds with an increase in wound-inducible polygalacturonase (PG) mRNA and enzyme activity previously reported, suggesting that oligogalacturonic acid (OGA) fragments produced by PG are triggering the H(2)O(2) response. Systemin, OGA, chitosan, and methyl jasmonate (MJ) all induce the accumulation of H(2)O(2) in leaves. Tomato plants transformed with an antisense prosystemin gene produce neither PG activity or H(2)O(2) in leaves in response to wounding, implicating systemin as a primary wound signal. The antisense plants do produce both PG activity and H(2)O(2) when supplied with systemin, OGA, chitosan, or MJ. A mutant tomato line compromised in the octadecanoid pathway does not exhibit PG activity or H(2)O(2) in response to wounding, systemin, OGA, or chitosan, but does respond to MJ, indicating that the generation of H(2)O(2) requires a functional octadecanoid signaling pathway. Among 18 plant species from six families that were assayed for wound-inducible PG activity and H(2)O(2) generation, 14 species exhibited both wound-inducible PG activity and the generation of H(2)O(2). Four species, all from the Fabaceae family, exhibited little or no wound-inducible PG activity and did not generate H(2)O(2). The time course of wound-inducible PG activity and H(2)O(2) in Arabidopsis thaliana leaves was similar to that found in tomato. The cumulative data suggest that systemic wound signals that induce PG activity and H(2)O(2) are widespread in the plant kingdom and that the response may be associated with the defense of plants against both herbivores and pathogens.